JaBÁ: A Java Bytecoder Analyser - Vincenzi, A. M. R.; Delamaro, M. E.; Simão, A. S.; Wong, W. E.; Maldonado, J. C. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2002)
Many existing control-flow and data-flow based techniques for software testing and program analysis require source code instrumentation. However, this approach may not be feasible for component-based software as some of its components can be commercial off-the-shelf products or developed by a third party, and therefore the corresponding source code is not always available. For programs written in Java, this problem can be solved by conducting instrumentation directly on bytecode, instead of on the Java source code. In this paper, we present a Java Bytecode Analyzer (JaBÁ), developed to help programmers and testers collect control-flow and dataflow based information through bytecode instrumentation.